Bone Marrow Aspirate Concentrate: Its Uses in Osteoarthritis - Kim, Gi Beom (Int J Mol Sci, 2020)
Human bone marrow (BM) is a kind of source of mesenchymal stem cells (MSCs) as well as growth factors and cytokines that may aid anti-inflammation and regeneration for various tissues, including cartilage and bone. However, since MSCs in BM usually occupy only a small fraction (0.001%) of nucleated cells, bone marrow aspirate concentrate (BMAC) for cartilage pathologies, such as cartilage degeneration, defect, and osteoarthritis, have gained considerable recognition in the last few years due to its potential benefits including disease modifying and regenerative capacity. Although further research with well-designed, randomized, controlled clinical trials is needed to elucidate the exact mechanism of BMAC, this may have the most noteworthy effect in patients with osteoarthritis. The purpose of this article is to review the general characteristics of BMAC, including its constituent, action mechanisms, and related issues. Moreover, this article aims to summarize the clinical outcomes of BMAC reported to date.